Sternal Uptake of 99mTc-MAA in Thoracic Outlet Syndrome. (December 2015) - Matsusaka, Yohji; Nakahara, Tadaki; Iwabuchi, Yu; Kameyama, Masashi; Murakami, Koji
Abstract : Abstract: 99m Tc-macroaggregated albumin (MAA) uptake in the vertebrae has been reported in central vein occlusion, although its sternal uptake is rarely seen. We present a case in which 99m Tc-MAA SPECT/CT showed spotty uptake in the sternum. Contrast-enhanced CT revealed marked narrowing of the left subclavian vein at the thoracic outlet with a developed collateral vein running, in the left anterior chest subcutaneous tissue, between the sternum and left axilla. In this case, IV injection of 99m Tc-MAA from the left forearm probably led to bone marrow uptake in the sternum due to retrograde venous flow through the collateral vein.